STRATEGI PENGEMBANGAN INDUSTRI KULIT OLEH DINAS PERDAGANGAN KOPERASI USAHA KECIL DAN MENENGAH DI KOTA PADANG PANJANG - Anto, Andi Tri; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In general, the Law of the Republic of Indonesia No. 3 of 2014 on the industry explains that national development should give maximum benefit to the welfare of the people. Since 2008, Memorandum of Understanding (MOU) has been signed between Directorate General of ILMTA-Ministry of Industry, West Sumatera Governor and Padang Panjang Mayor. In the MoU described the division of tasks and obligations of each party to work synergistically implement the Leather Industry Development Program Padang Panjang City.In Strategy theory, Rangkuti explains the principle of strategy can be grouped based on 3 (three) types, among others: Management Strategy, Investment Strategy, And Business Strategy.The research method used in this research is qualitative research. With the technique that is done snow ball sampling, to key informant in this research. In this writing, the key informant is the Head of Department of Trade Cooperative Small and Medium Enterprises Padang Panjang, Head of Industry Trade and Promotion, Industry Leather Industry and then analyze and process data.Based on the research and discussion that the researchers did in the field, it was found that the Leather Industry Development Strategy by the Department of Trade Cooperative Small and Medium Enterprises in Padang Panjang has not been implemented maximally, it is influenced by limitation of business capital, the competition of leather industry products, the limited skills of leather entrepreneurs, and the role of government is less than maximun.Keywords: Strategy, Development, Leather Industry